Antiepidermal Growth Factor Receptor Monoclonal Antibodies: Applications in Colorectal Cancer. (8th October 2012) - Azizi, Efat; Kittai, Adam; Kozuch, Peter
Abstract : Patients with metastatic colorectal cancer have a poor prognosis and present a challenge to clinicians. The role of the antiepidermal growth factor receptor (EGFR) pathway in tumorogenesis and tumor progression has been well defined. This paper will review the use of anti-EGFR monoclonal antibodies in the treatment of operable, as well as metastatic colorectal cancer both in the setting of KRAS mutation unselected patients and later in KRAS wild-type patients. Active investigations designed to further identify predictive biomarkers that may be potentially druggable are reviewed as well.